Web Program Testing Using Selenium Python: Best Practices and Effective Approaches - Rusdiansyah, Rusdiansyah; Suharyanti, Nining; Supendar, Hendra; Tuslaela, Tuslaela (Politeknik Ganesha Medan, 2024)
A critical component of software development is testing programs on websites to make sure they run, are secure, and meet user expectations. This article explores efficient methods and best practices for utilizing Selenium with the Python programming language to perform program testing on websites. This study shows the outcomes of Selenium WebDriver-based automated testing on two webpages: https://demoqa.com/text-box and https://demoqa.com/login. Testing was done to assess Selenium's dependability and performance when it comes to completing text fields and completing the login procedure. The goal of the study is to evaluate Selenium WebDriver's dependability and effectiveness in basic testing jobs while spotting any issues that may arise. Using the appropriate locator to fill in text boxes efficiently using Selenium WebDriver ensures that the operation proceeds without major hiccups. The effective completion of the login procedure on the https://demoqa.com/login page further demonstrates the dependability of Selenium WebDriver for handling increasingly complicated interactions, including login. According to the analysis's findings, Selenium WebDriver is a dependable and efficient solution for test automation that performs consistently and steadily under a range of conditions. The research's conclusions highlight how crucial it is to use automation technologies in order to ensure software quality and boost testing effectiveness. Software engineers can detect issues more rapidly and completely test the functionality of applications with Selenium WebDriver, which enhances the overall quality of software development